Computational anatomy of the proximal humerus: An ex vivo high-resolution peripheral quantitative computed tomography study - Kamer, Lukas (J Orthop Translat, 2015)
BACKGROUND/OBJECTIVE: Spatial knowledge of the anatomy of the proximal humerus is critical for effective treatment, particularly in patients affected by fragility fractures. High-resolution peripheral quantitative computed tomography (HR-pQCT) imaging with medical image processing techniques enable three dimensional (3D) analysis of volumetric bone mineral density (vBMD) of bones of different sizes and shapes. METHODS: To elucidate the bony anatomy and to create 3D reference data, we conducted a computerized HR-pQCT-based study in intact postmortem samples of the proximal humerus to highlight the anatomy with particular emphasis on the size, shape, and bone stock distribution pattern. Fifty-eight defrozen intact humerus samples from 28 female and 30 male donors, who were aged 61–98 years old (mean age ± standard deviation, 80.6 ± 9 years), were scanned in the proximal third using the extended standard HR-pQCT protocol. A 3D statistical bone and averaged bone density models with low, middle, and high total vBMDs were computed. We examined the 3D patterns of size and shape variations using principal component analysis, and the vBMD distributions and variabilities using volume-rendering and virtual bore probing. RESULTS: The computer models revealed a highly variable bony anatomy in which size was the predominant variation in the first principal component (PC). In the second PC, we observed notable variabilities in the shape of the head and shaft inclination. A distinct 3D pattern of bone stock distribution was detected in which the lowest vBMD values were identified in the medullary cavity, middle values were identified in the central zone, and the highest values were identified in the cortex and humeral head—particularly in the subarticular zones. In the presence of bone loss, the vBMD values were ubiquitously decreased, but the pattern of 3D bone stock distribution was maintained. CONCLUSION: The new anatomical 3D data that we acquired will improve the understanding of the normal bony anatomy of the proximal humerus. The extended HR-pQCT protocol and computer models may be used for other skeletal sites and used as 3D reference models that can be applied to systematically improve implant design and anchorage.